2017
DOI: 10.1155/2017/5637923
|View full text |Cite|
|
Sign up to set email alerts
|

A Higher Ovarian Response after Stimulation for IVF Is Related to a Higher Number of Euploid Embryos

Abstract: This study has analysed the relationship between ovarian response and the number of euploid embryos. This is a post hoc analysis of a subset of data generated during a prospective cohort study previously published. Forty-six oocyte donors were subjected to ovarian stimulation with 150 IU of rFSH and 75 IU of hp-hMG in a GnRH agonist long protocol. Preimplantation genetic screening was performed in all viable embryos. We observed a positive relationship between ovarian response and the number of euploid embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
2
31
0
2
Order By: Relevance
“…Nine studies analyzing the impact of COS on euploidy rates have been published (Baart et al 2007, Verpoest et al 2008, Rubio et al 2010, Massie et al 2011, Ata et al 2012, Labarta et al 2012, 2017, Barash et al 2017, Sekhon et al 2017. Labarta et al recently maintained that aneuploidy rate did not increase with ovarian response or gonadotropin dosage (Labarta et al 2017). Also, the authors observed that the number of euploid embryos was inversely related to the ovarian sensitivity index (Huber et al 2013), which correlates the amount of gonadotropins needed per oocyte obtained (Labarta et al 2017).…”
Section: Association Of Ovarian Stimulation and Aneuploidymentioning
confidence: 97%
See 3 more Smart Citations
“…Nine studies analyzing the impact of COS on euploidy rates have been published (Baart et al 2007, Verpoest et al 2008, Rubio et al 2010, Massie et al 2011, Ata et al 2012, Labarta et al 2012, 2017, Barash et al 2017, Sekhon et al 2017. Labarta et al recently maintained that aneuploidy rate did not increase with ovarian response or gonadotropin dosage (Labarta et al 2017). Also, the authors observed that the number of euploid embryos was inversely related to the ovarian sensitivity index (Huber et al 2013), which correlates the amount of gonadotropins needed per oocyte obtained (Labarta et al 2017).…”
Section: Association Of Ovarian Stimulation and Aneuploidymentioning
confidence: 97%
“…Labarta et al recently maintained that aneuploidy rate did not increase with ovarian response or gonadotropin dosage (Labarta et al 2017). Also, the authors observed that the number of euploid embryos was inversely related to the ovarian sensitivity index (Huber et al 2013), which correlates the amount of gonadotropins needed per oocyte obtained (Labarta et al 2017). Several non-randomized studies have also determined that aneuploidy rate was not associated with the number of embryos generated (Ata et al 2012, Barash et al 2017, Sekhon et al 2017.…”
Section: Association Of Ovarian Stimulation and Aneuploidymentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study in a population of young normovulatory women showed that a high ovarian response after controlled ovarian stimulation with moderate gonadotropin doses did not increase the embryo aneuploidy rate. Indeed, the higher the ovarian response, the more the euploid embryos obtained [80]; the remaining question is whether this can also be extrapolated to infertile patients with good ovarian reserve.…”
Section: Ovarian Stimulation and The Incidence Of Embryo Aneuploidymentioning
confidence: 99%